(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In the European Union government debt issues are combined with Maastricht requirements, whom the majority of member states are not following. At the same time in the case of Latvia in the summer of 2013 the specific saving bond system were introduces and government started to attract resident investments. From authors perspective the system, where each resident can invest money in its own country is the right direction for country development. At the same time there are world wide experience of saving bond instrument and by having the best world practice, the system can be improved. As the first challenge for government is to understand the quantity of financial resources in the household accounts. That follows by the interest rates for deposits. At the end the government can offer some additional bonus programs, to support its residents from one side, and to receive their votes on next elections from other side. The main thing is the way how households are saving their money, as if there is investments in corporate debt or equity, then, by attracting money for saving bonds, government decreases economic activity. At the same time, if the money comes from deposits, it affects profit of banks and supports diversifications on residents investment portfolios.